Archie s Pals n Gals Double Digest 135 - Ed. Gorelick, Victor (Archie Comic Publications Inc, 2009)
It is Reggie's turn to shine as star of Archie Comics's Latest new look story line.But will his breakout performance leave him broken-hearted?
Keywords: Juvenile literature-Fiction